Validity & Reliability of Stunting Questionnaire for Toddlers in Rural Areas of Southwest Papua - Hasim, Nur Hafni; Inayah, Iin; Nurjannah, Nunung (Babali Publisher, 2023)
Introduction: Stunting can ruin the future of children. However, changes immediately impact the stage of development of the child. This show needs to develop a valid and reliable instrument that can be used for current causes of stunting in rural areas. Purpose: The papers try to analyse development instruments to find out the factors that cause stunting in rural areas. Methods: The study was conducted as a shape survey, with quantitative data analysis to get an outlook measurement validity and reliability instrument built practically with the cross-sectional method. Only mothers who have children of their own recruited toddlers to study this. Study this using a questionnaire. Reliability has been counted using Cronbach's alpha Findings: The child's age, height, and weight are valid in determining biological factors in stunting situations. Total room at home, job head family, and education Mother is a sub-variable that does not describe socioeconomic factors that cause stunting. Family history planned no is a supporting sub-variable for dig reason stunting behaviours. Conclusions: This project was conducted to design and evaluate a questionnaire to determine stunting factors in rural society. The investigation results show that the questionnaire is worthy of identifying factors that cause stunting in rural society. The findings will be interesting for policymakers and academic researchers. Limitations central to the study include a low interpretation of society as a respondent. Despite limitations, this study shows that biological, socioeconomic, and behavioural factors cause stunting in rural regions. Far more necessary work was conducted to determine stunting factors in the rural region. Because of it, there is a definite need to do an in-depth interview.